Transformation of Financial Relations of Business Entities in the Context of Globalization - VYHOVSKA, Nataliya H.; ALEKSANDROVA, Mariya M.; DOVGALIUK, Vita V.; DIACHEK, Svitlana M.; LYTVYNCHUK, Iryna V. (Journal of Advanced Research in Law and Economics; Vol 9 No 8 (2018): JARLE Volume IX Issue 8(38) Winter 2018DO - 10.14505//jarle.v9.8(38).36, 2019)
The formation of the activities of business entities in the context of globalization takes place in conditions of not only competition, but also a number of processes that are identified with support from public authorities. The relevance of the research is determined by the fact that support measures aimed at creating artificial means of increasing the competitiveness of business entities are being fully implemented. This position is inherent even in market-type economies, which is defined as a non-market competitive advantage. The novelty of the research lies in the idea that the subject of economic relations receives competitive advantages in the course of competition and increasing their positions in the open market. In the field of global trade, it is advisable to implement this using a game model, since on the basis of scenario forecasts and a game development model, the functions of strengthening the position of the enterprise are implemented. The authors provide a calculation of the model for the global market, factoring in the costs of not just the output, but also analyzing the costs, the amount of which depends on state assistance. The practical significance of the research is determined by the fact that such a model can be applied in a global context and implemented as an instrument of transparency in international trade and economic relations.